Role of nitric oxide in response to high salinity in eelgrass - Xinfang Lv; Pei Yu; Jie Pan; Xianyan Wang; Yuchun Li (Current Plant Biology, 2023)
Nitric oxide (NO) is an essential molecule for plants, and we have found that NO is mainly synthesized by the nitrate reductase (NR) pathway in eelgrass. To understand the influence of NO on eelgrass, the proline content, the expression of the Na+/H+ antiporter and H+-ATPase, and antioxidant activities were examined under different conditions. The results showed that NO significantly affected these physiological indicators in eelgrass, which played a positive role in eelgrass adaptation to the marine environment. Using RNA-seq, we performed a comprehensive analysis of the genes involved in the NO effects on eelgrass adaptation to high salinity environments. The expression of myosin and glutamine dumper decreased most significantly after inhibiting the NR-dependent NO synthesis. This study shows that the physiological metabolic activities in eelgrass, such as signal transduction process and amino acid metabolism, are closely related to NO under high salinity.